Gambaran Program Percepatan Penurunan Stunting di Wilayah Kerja Puskesmas Tawiri - Zulfikar Lating; Rahma Tunny; Siti Rapia Latuconsina (Calory Journal Medical Laboratory Journal, 2023)
Efforts to reduce the prevalence of stunting are carried out through two interventions, namely specific nutrition interventions and sensitive nutrition interventions. Specific nutrition interventions are interventions that are directly targeted at households in the First 1,000 Days of Life (HPK). Meanwhile, sensitive nutrition interventions are interventions aimed at various development activities outside the health sector. The target is the general public. This type of research is field research with a qualitative descriptive approach. The informants in this research were 8 people including stunting program holders, nutrition officers from community health centers, posyandu cadres, stunting cadres, PKK cadres, and the State Government. The results of the research show that the Tawiri Community Health Center has implemented various specific nutritional intervention programs, including distribution of TTD for adolescent girls, distribution of PMT for pregnant women with KEK, PMT for toddlers, counseling, sweeping for pregnant women, classes for pregnant women, PHBS counseling, as well as counseling on the use of clean water. . However, giving PMT biscuits to toddlers is not appropriate because the consumption standard is 3 boxes per month. The State Government as implementer of specific nutrition interventions also contributes to reducing stunting by making efforts in the form of activating cadres, allocating village funds to resolve stunting. Obstacles in implementing the stunting reduction acceleration program are the minimal level of knowledge of parents or mothers who have stunted toddlers, as well as the low income of parents which causes inadequate nutritional intake for children.